Examining Teacher Job Satisfaction and Principals’ Instructional Supervision Behaviours: A Comparative Study of Turkish Private and Public School Teachers - Sungu, Hilmi; Ilgan, Abdurrahman; Parylo, Oksana; Erdem, Mustafa (Alberta Journal of Educational Research, 2014)
In spite of a strong body of research examining teacher job satisfaction and teachers’ assessment of their principals’ behaviours, most studies focus on the educational systems in the first world countries. This quantitative study focuses on a lesser-examined educational context by comparing school teachers’ job satisfaction levels and principals’ instructional supervision behaviours in Turkish private and public schools. The results suggest that for all examined demographical characteristics of participating teachers (e.g., gender, school level, subject matter, and years of teaching); private school teachers had higher levels of job satisfaction and assessed their principals’ instructional supervision behaviours higher than did public school teachers. These findings suggest there are more favourable working conditions in Turkish private schools than in public schools and support research trends on the topic of teacher job satisfaction from other countries. L’important corpus de recherche qui porte sur la satisfaction au travail des enseignants et leurs évaluations du comportement des directeurs a surtout étudié les systèmes d’éducation dans les pays du premier monde. Cette étude quantitative se situe dans un contexte éducatif moins étudié et compare les niveaux de satisfaction au travail des enseignants et le comportement des directeurs relatif à la supervision professionnelle dans des écoles privées et publiques en Turquie. Les résultats indiquent que pour toutes les caractéristiques démographiques étudiées (par ex. sexe, niveau scolaire, matière, nombre d’années d’enseignement), les enseignants dans les écoles privées ressentent plus de satisfaction au travail et estiment davantage le comportement de leurs directeurs relatif à la supervision professionnelle que les enseignants dans les écoles publiques. Ces résultats portent à croire qu’en Turquie, les conditions de travail dans les écoles privées sont plus favorables que celles dans les écoles publiques, ce qui s’inscrit dans les tendances en recherche portant sur la satisfaction au travail des enseignants dans d’autres pays.